The Use of Deixis in “Five Feet Apart” Movie - Widayanti, Ni Ketut Feni Kresna; Ediwan, I Nyoman Tri (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This article entitled “The Use of Deixis in “Five Feet Apart” Movie” the study aims to analyze the types of deixis used in the "Five Feet Apart" movie as well as to explain the most dominant deixis used in the "Five Feet Apart" movie. The data of this study were taken from the movie and the script of the movie "Five Feet Apart" directed by Justin Baldoni, a 2019 American romantic drama. In the process of collecting data, documentation method was used. The data were analyzed using a descriptive qualitative and pragmatic approach.  This research also uses a simple quantitative method to count the data. The researcher used the theory of pragmatics proposed by Levinson (1983) as the main theory and supported by other supporting theories. This research shows that five types of deixis are used in the "Five Feet Apart" movie. The researcher found there are; 694 person deixis (82%), 29 spatial deixis (3%), 21 temporal deixis (2%), 78 discourse deixis (9%), and 21 social deixis (2%). The most dominant deixis used in the "Five Feet Apart" movie is person deixis which consists of 694 deictic expressions and the word "I" is a deictic expression that appears the most in the "Five Feet Apart" movie that includes in the first singular person deixis. Keywords: Pragmatics, Deixis, Movie, Five Feet Apart